Acceleration of Carbon Fixation in Chilling-Sensitive Banana under Mild and Moderate Chilling Stresses - Liu, Jing; Takáč, Tomáš; Yi, Ganjun; Chen, Houbin; Wang, Yingying; Meng, Jian; Yuan, Weina; Tan, Yehuan; Ning, Tong; He, Zhenting; Šamaj, Jozef; Xu, Chunxiang (International journal of molecular sciences, 2020)
Banana is one of the most important food and fruit crops in the world and its growth is ceasing at 10-17 °C. However, the mechanisms determining the tolerance of banana to mild (>15 °C) and moderate chilling (10-15 °C) are elusive. Furthermore, the biochemical controls over the photosynthesis in tropical plant species at low temperatures above 10 °C is not well understood. The purpose of this research was to reveal the response of chilling-sensitive banana to mild (16 °C) and moderate chilling stress (10 °C) at the molecular (transcripts, proteins) and physiological levels. The results showed different transcriptome responses between mild and moderate chilling stresses, especially in pathways of plant hormone signal transduction, ABC transporters, ubiquinone, and other terpenoid-quinone biosynthesis. Interestingly, functions related to carbon fixation were assigned preferentially to upregulated genes/proteins, while photosynthesis and photosynthesis-antenna proteins were downregulated at 10 °C, as revealed by both digital gene expression and proteomic analysis. These results were confirmed by qPCR and immunofluorescence labeling methods. Conclusion: Banana responded to the mild chilling stress dramatically at the molecular level. To compensate for the decreased photosynthesis efficiency caused by mild and moderate chilling stresses, banana accelerated its carbon fixation, mainly through upregulation of phosphoenolpyruvate carboxylases.
Keywords: transkriptom; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Transcriptome; Photosynthesis; Phosphoenolpyruvate Carboxylase; Plant Proteins; fotosyntéza; rostlinné proteiny; Cold-Shock Response; Musa; Up-Regulation; fosfoenolpyruvátkarboxylasa; banánovník; reakce na chladový šok; upregulace